Zin-P1 / P2 double-layer composite fiber electrode, preparation thereof and application of zinc-P1 / P2 double-layer composite fiber electrode in negative-electrode-free zinc battery
Through the use of zinc -P1/P2 double-layer composite fiber electrodes in the balm-free zinc battery, the optimization control of two sections of electrostatic spinning technology and zinc salt and polymers is used to solve. A series of issues, especially low temperature performance, have achieved significant improvement of performance.
Patent Information
- Application Number
- CN202411584159.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-07
AI Technical Summary
During the cycle, negative electrode-free zinc batteries face problems such as hydrogen evolution reaction, dendrite growth, dead zinc evolution, insufficient energy density, and low temperature performance.
The preparation method of the zinc-P1/P2 double-layer composite fiber electrode is adopted, and the zinc-P1 layer and P2 layer of the zinc-P1 layer are formed through two sections of static spinning technology, which combines the optimization control of zinc salt and polymers to form a good hierarchical fusion interface.
Effectively improves the performance of non -polar zinc batteries, especially low temperature performance, reducing hydrogen analysis reactions, chief crystal growth and dead zinc evolution, and improving energy density.
Smart Images

Figure CN119381394A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of zinc batteries, and in particular relates to a zinc battery without a negative electrode. Background Art
[0002] Zinc-ion batteries have the advantages of high energy density, long cycle life, low cost and environmental protection, so they have broad application prospects in electric vehicles, energy storage systems, mobile devices and other fields. Compared with traditional lithium-ion batteries, zinc-ion batteries have lower costs, and zinc is a widely available metal with abundant resources and no shortage of supply. With the continuous development of technology and the continuous expansion of applications, zinc-ion batteries will become one of the important representatives of new batteries in the future. However, the energy density of zinc-ion batteries is currently insufficient, and zinc metal suffers from severe dendrite growth, electrode side reactions and gas production during the cycle, which seriously endangers the safety of the battery.
[0003] At present, researchers have carried out a lot of research work on improving zinc negative electrodes and developing new electrolytes, but the corresponding problems have not been completely solved. The negative electrode-free battery solution avoids the use of zinc metal, which can properly solve the problems of zinc metal dendrite growth and interface reaction. In addition, the negative electrode-free battery has a smaller volume and mass, which can greatly improve the energy density of the new battery.
[0004] However, the existing research on negative electrode-free batteries is still immature, and the few methods are mainly to form a zinc layer or a zinc-philic layer on an existing current collector. For example, a Chinese patent document with publication number CN113013496A discloses a negative electrode-free zinc battery with high safety factor and low cost and its application, wherein the negative electrode-free zinc battery is composed of a positive electrode current collector, a positive electrode, a separator, an electrolyte, and a negative electrode current collector.
[0005] The Chinese patent document with publication number CN115764005A discloses a high-performance negative electrode-free aqueous zinc metal battery based on a composite layered negative electrode current collector, comprising the steps of: coating a conductive layer on the surface of a zinc metal deposition substrate; preparing a guiding layer solvent and coating it on the conductive layer by a coating method, and then drying it in an oven. A Chinese patent document disclosed a negative electrode-free zinc metal battery with a zwitterionic polymer as a binder, wherein the negative electrode-free zinc metal battery is assembled from a positive electrode, a separator, a negative electrode current collector loaded with a zwitterionic polymer binder, and an electrolyte. A Chinese patent document with publication number CN113036152A disclosed a high energy density, high safety negative electrode-free zinc metal battery and its preparation method and application, wherein the zinc metal battery uses a negative electrode current collector with a zinc-philic layer, wherein the zinc-philic layer is one or more of a zinc-philic ion, electron, or mixed ion conductor layer.
[0006] In summary, the existing technology has disclosed a small number of negative electrode-free zinc batteries, but the existing technology still needs to face steps such as hydrogen evolution reaction, dendrite growth, dead zinc evolution, and insufficient energy density. The research on cycle stability, especially low-temperature stability, is still a blank in the industry. Summary of the invention
[0007] In view of the problems faced by negative electrode-free zinc metal batteries during the cycle process, such as hydrogen evolution reaction, dendrite growth, dead zinc evolution, insufficient energy density, and low-temperature performance, the first purpose of the present invention is to provide a method for preparing a zinc-P1 / P2 double-layer composite fiber electrode suitable for the characteristics of negative electrode-free zinc batteries, so as to improve their performance in negative electrode-free zinc batteries.
[0008] The second object of the present invention is to provide a zinc-P1 / P2 double-layer composite fiber electrode prepared by the preparation method and its application in a negative electrode-free zinc metal battery.
[0009] The third object of the present invention is to provide a negative electrode-free zinc metal battery comprising the zinc-P1 / P2 double-layer composite fiber electrode.
[0010] Compared with zinc ion batteries using zinc metal, negative electrode-free batteries have the advantages of low cost, high mass energy density and high volume energy density, but their key problem is that the zinc ions on the negative electrode side have poor reversibility and poor kinetic performance, resulting in poor wide temperature range rate performance. In response to this problem, the present invention has provided the following solutions after research: A method for preparing a zinc-P1 / P2 double-layer composite fiber electrode, comprising obtaining a spinning solution A in which a zinc salt and a polymer P1 are dissolved, and obtaining a spinning solution B in which a polymer P2 is dissolved; The first stage of electrostatic spinning is carried out using spinning solution A to obtain a zinc-P1 layer; the second stage of electrostatic spinning is carried out using the zinc-P1 layer as a substrate using spinning solution B to form a P2 layer on the surface of the zinc-P1 layer, which is then dried to obtain the zinc-P1 / P2 double-layer composite fiber electrode.
[0011] The present invention innovatively forms the zinc-P1 layer (three-dimensional framework layer 1) based on electrospinning, and further uses it as a substrate, and forms the P2 layer (three-dimensional framework layer 2) on its surface based on electrospinning, wherein the P2 layer gives the double-layer material a good blending interface under the action of electrospinning. The present invention's research shows that based on the two-stage electrospinning method, combined with the joint control of the spinning solution components, a good hierarchical fusion interface can be formed, which helps to reduce hierarchical impedance, helps to adapt to the problems faced by the use of negative-electrode zinc batteries, helps to reduce the deficiencies such as hydrogen evolution reaction, dendrite growth, dead zinc evolution and energy density, and can effectively improve the performance of the prepared material in negative-electrode zinc batteries, especially low-temperature performance.
[0012] The zinc salt is one or more of zinc chloride, zinc trifluoromethanesulfonate, zinc sulfate, bis(trifluoromethanesulfonyl)zinc, zinc acetate, and zinc perchlorate; preferably at least one of zinc trifluoromethanesulfonate and bis(trifluoromethanesulfonyl)zinc. Studies have shown that based on the two-stage spinning process, further coordinated with the optimized control of the zinc salt, it is helpful to further improve the low temperature performance of the prepared material in the negative electrode-free zinc battery.
[0013] In the present invention, the polymer P1 and the polymer P2 are independently one or more of polyacrylonitrile PAN, polyacrylic acid PAA, and polyvinyl pyrrolidone PVP.
[0014] Preferably, the polymer P1 and polymer P2 are different polymers. Further preferably, the polymer P1 is PAN, and the polymer P2 is PAA. Based on the two-stage spinning process, further optimizing and controlling the polymers P1 and P2 helps to further improve the interface physical and chemical structure, and helps to further improve the low temperature performance of the prepared material in the negative electrode-free zinc battery.
[0015] In the present invention, the solvent in the spinning solution A and the spinning solution B includes one or more of N,N-dimethylformamide DMF, N,N-dimethylacetamide DMA and the like.
[0016] Preferably, the solvent in the spinning solution A is DMF, and the solvent in the spinning solution B is DMA. Based on the two-stage spinning process, further optimizing and controlling the solvent is helpful to further improve the interface physical and chemical structure, and to further improve the low temperature performance of the prepared material in the negative electrode-free zinc battery.
[0017] Preferably, in the spinning solution A, the zinc salt content is 5-30 wt .%, and can be further 10-25 wt .%; the polymer P1 content is 1-40 wt .%, and can be further 10-25 wt .%. The zinc salt content refers to the weight content of the zinc salt relative to the solvent. The polymer P1 content refers to the weight percentage of the polymer P1 relative to the solvent.
[0018] Preferably, in the spinning solution B, the content of polymer P2 is 5-50 wt %., and can further be 10-25 wt %. The polymer P2 content refers to the weight percentage of polymer P2 relative to the solvent.
[0019] In the present invention, the voltage of electrospinning is 12-18 kV, and can further be 14-16 kV.
[0020] Preferably, the thickness of the zinc-P1 layer is 20-100 μm, and further can be 40-60 μm; the thickness of the P2 layer is 200-700 μm, and further can be 300-500 μm, and further can be 350-450 μm. Studies have shown that at the preferred thickness, the synergy of the structure can be further enhanced, and its low-temperature cycle performance can be further improved.
[0021] In the present invention, the speed of the first electrospinning stage and the second electrospinning stage is 0.01-0.05 mm / min. -1 Preferably, the spinning speed of the first stage of electrospinning is 0.01-0.03 mm min -1 The spinning speed of the second electrospinning stage was 0.03-0.05 mm min -1 , and the second electrospinning rate is 1.5 to 2.5 times that of the first electrospinning rate. Studies have shown that under the combined control of the preferred spinning rate, the hierarchical synergy can be further enhanced, and the low-temperature and wide-temperature stability of the prepared material can be further improved.
[0022] In the present invention, the drying temperature is 45-70°C.
[0023] The invention also provides a zinc-P1 / P2 double-layer composite fiber electrode prepared by the preparation method.
[0024] The material of the present invention comprises a zinc-P1 layer and a P2 layer compounded on the surface thereof; wherein the zinc-P1 layer is a fiber layer formed by interlacing and weaving polymer P1 fibers dispersed with zinc salt; and the P2 layer is a fiber layer formed by interlacing and weaving polymer P2 fibers, and there is a special fusion interface between the two fiber layers. The research of the present invention shows that the material prepared by the preparation method can unexpectedly adapt to the application requirements of negative electrode-free zinc batteries, and can unexpectedly improve its structural stability, especially helping to improve its low temperature stability.
[0025] The present invention also provides an application of the zinc-P1 / P2 double-layer composite fiber electrode prepared by the preparation method, which is used to prepare a negative electrode-free zinc battery; Preferably, the zinc-P1 / P2 double-layer composite fiber electrode and the positive electrode are combined to form a battery cell of a negative electrode-free zinc battery, wherein the surface of the P2 layer of the zinc-P1 / P2 double-layer composite fiber electrode is close to the positive electrode side.
[0026] The positive electrode may be a material known in the industry. For example, the positive electrode active material may be one or more of manganese dioxide, vanadium pentoxide, and ammonium vanadate.
[0027] The negative electrode-free zinc battery further comprises an aqueous electrolyte. The electrolyte in the aqueous electrolyte comprises one or more solutions of zinc chloride ZnCl2, zinc trifluoromethanesulfonate Zn(CF3SO3)2, zinc sulfate ZnSO4, bistrifluoromethanesulfonyl zinc Zn(TFSI)2, zinc acetate Zn(CH3COO)2, zinc perchlorate Zn(ClO4)2, etc.
[0028] In the present invention, the battery does not need to include a zinc negative electrode or a negative electrode containing zinc metal.
[0029] The present invention also provides a negative electrode-free zinc battery, comprising a battery cell composed of a zinc-P1 / P2 double-layer composite fiber electrode and a positive electrode, and an electrolyte for soaking the battery cell, wherein the surface of the P2 layer of the zinc-P1 / P2 double-layer composite fiber electrode is close to the positive electrode side.
[0030] Beneficial Effects
[0031] The present invention is based on the combination of the two-stage electrospinning and the process, which can improve the adaptability of the prepared material in the negative electrode-free zinc battery and can effectively improve the performance of the prepared material in the negative electrode-free zinc battery, especially the low-temperature performance.
[0032] The present invention can further strengthen the hierarchical interface and structure of the material through the combined control of polymers P1 and P2, zinc salt and two-stage spinning processes, which helps to further enhance the performance of the prepared material in a negative electrode-free zinc battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 Graph showing the cycle performance of the full battery of Example 1 and Comparative Example 1 at 25°C; Figure 2 The cycle performance diagram of the full battery of Example 1 and Comparative Example 1 at -20°C; Figure 3 Graph showing symmetrical battery cycle performance of Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0034] An optional method for preparing a zinc-P1 / P2 double-layer composite fiber electrode of the present invention: the preparation steps are as follows: I. dissolving an organic solvent, polymer P1 and zinc salt to obtain a spinning solution A; dissolving an organic solvent and polymer P2 to obtain a spinning solution B, II. The spinning solution A is spun onto the surface of the aluminum foil by electrospinning, and the thickness is controlled by the spinning time to obtain the first layer of material (zinc-P1 layer); III. Then, the spinning solution B is spun onto the surface of the first layer of material to form a P2 layer; IV. The obtained spinning layer is dried at high temperature, and the zinc-P1 / P2 double-layer composite fiber electrode is obtained after stripping the aluminum.
[0035] The organic solvent described in step I is one or more of N,N-dimethylformamide DMF, N,N-dimethylacetamide DMA, etc.
[0036] The polymer P1 described in step I is one or more of polyacrylonitrile PAN, polyacrylic acid PAA, polyvinyl pyrrolidone PVP, etc.
[0037] The mass ratio of the polymer P1 and the organic solvent in step I is (0.01-0.5):1, and can further be 0.1-0.2:1.
[0038] The zinc salt described in step I is one or more of zinc chloride ZnCl2, zinc trifluoromethanesulfonate Zn(CF3SO3)2, zinc sulfate ZnSO4, bistrifluoromethanesulfonyl zinc Zn(TFSI)2, zinc acetate Zn(CH3COO)2, zinc perchlorate Zn(ClO4)2, etc.
[0039] The molar amount of the zinc salt described in step I is (0.1~3):1 of the total mass of the mixed solution B, and can further be 0.1~0.2:1.
[0040] The electrospinning voltage in steps II and III is 12-18 kV, and the spinning speed is 0.01-0.05 mm min -1 The spinning thickness is 0.01~50μm, and the higher the spinning voltage, the slower the spinning speed.
[0041] The weaving time of step II is 2-4 hours, or the weaving thickness is controlled at 20-100 μm; the weaving time of step III is 5-20 hours, or the weaving thickness is controlled at 200-700 μm.
[0042] The drying temperature in step IV is 45-70° C., air atmosphere, and forced air drying.
[0043] In the present invention, the raw materials can all be commercially available components known in the field of zinc batteries.
[0044] Example 1
[0045] Step 1: Control the mass ratio of polymer P1 (polyacrylonitrile PAN) to solvent (N,N-dimethylformamide DMF) to 0.11:1, then add a certain amount of zinc trifluoromethanesulfonate Zn(CF3SO3)2 to dissolve in the mixed solution and mix evenly, so that the zinc salt is 14wt.% of the weight of the solvent, to obtain spinning solution A; Mixing polymer P2 (polyacrylic acid PAA) and N,N-dimethylacetamide DMA to form a spinning solution B, wherein the weight ratio of polymer P2 to solvent is 0.11:1; Step 2: Use electrospinning to spin the spinning solution A onto the surface of the aluminum foil, control the spinning voltage to 15 kV, and the spinning speed to 0.02 ml min -1 , the spinning thickness is 50 μm, forming the first fiber layer (Z side); Step 3: Continue to spin the spinning solution B on the first fiber layer (Z side) to form the second fiber layer (G side), wherein the spinning voltage is 15 kV and the spinning speed is 0.04 ml min -1 The spinning thickness was 400 μm. After the double-layer spun product was dried at 50°C, the aluminum foil was peeled off to obtain a double-layer material.
[0046] V2O5 was used as the positive electrode, and the mass ratio of V2O5: carbon black: PVDF was 7:2:1. The mixture was uniformly mixed to form a slurry, which was uniformly coated on a titanium foil, which was cut into a positive electrode sheet with a diameter of 12 mm. The prepared double-layer material was used as the electrode sheet and the positive electrode sheet was composited (the G surface was close to the positive electrode sheet), and assembled into a CR2025 type button battery in the air, which was the full battery of Example 1. The double-layer material was then assembled into a symmetrical battery (two pieces of the prepared double-layer material were used as electrodes, wherein the G surfaces of the two pieces of double-layer material were close to each other), which was the half-battery of Example 1. The electrolyte of the full battery and the half-battery was 1M zinc sulfate aqueous solution.
[0047] Comparative Example 1 Compared with the full cell and half cell of Example 1, the difference is that the comparative cell uses zinc metal instead of the double-layer material described in the present invention as the negative electrode. On this basis, a conventional separator (such as a PAN separator with a thickness of 450±10μm) is arranged between the electrodes and assembled into a CR2025 button cell under the same conditions.
[0048] The above batteries were subjected to charge and discharge cycle tests under the same test equipment and test conditions, wherein the battery test voltage range was 0.2~1.6V and the test temperature was 25℃ and -20℃. Figure 1 The first discharge capacity of the battery in Example 1 at 25°C is 260 mAh / g, and the capacity retention rate is 57% after 1000 cycles. The discharge capacity of the battery in Comparative Example 1 is 223 mAh / g, and the discharge capacity is 10% after 1000 cycles. Figure 2 The initial discharge capacity of Example 1 at -20°C is 125 mAh / g, while the discharge capacity of the comparative battery under the same conditions is 78 mAh / g. Figure 3 It shows that the symmetrical battery of Example 1 can cycle for more than 1100 hours at -20°C, while the battery of Comparative Example 1 short-circuit after 400 hours of cycling.
[0049] Example 2
[0050] Compared with Example 1, the only difference is that the zinc salt used is bis(trifluoromethanesulfonyl)zinc(TFSI)2, and the mass ratio remains unchanged. Other operations, parameters and tests are the same as those in Example 1, and the results are: The first discharge capacity at 25°C was 252 mAh / g, and the capacity retention rate was 53% after 1000 cycles. The initial discharge capacity at -20°C was 118 mAh / g, and the symmetrical battery cycled for 900 hours.
[0051] Example 3
[0052] Compared with Example 1, the only difference is that the organic solvent used in solution A (spinning solution A) is N,N-dimethylacetamide DMA, and the organic solvent used in solution B (spinning solution B) is DMF, and their mass ratio remains unchanged. Other operations, parameters and tests are the same as in Example 1, and the results are: The first discharge capacity at 25°C was 251 mAh / g, and the capacity retention rate was 54% after 1000 cycles. The initial discharge capacity at -20°C was 116 mAh / g, and the symmetrical battery cycle was 920 hours.
[0053] Example 4
[0054] Compared with Example 1, the only difference is that polymer P1 uses polyacrylic acid PAA and polymer P2 uses PAN, and their mass ratio remains unchanged. Other operations, parameters and tests are the same as in Example 1, and the results are: The first discharge capacity at 25°C was 248 mAh / g, and the capacity retention rate was 50% after 1000 cycles. The initial discharge capacity at -20°C was 112 mAh / g, and the symmetrical battery cycled for 880 hours.
[0055] Example 5
[0056] Compared with Example 1, the only difference is that the zinc salt is 20wt.% of the weight of the spinning solution A solvent. The first discharge capacity of the cycle at 25°C is 256mAh / g, and the capacity retention rate after 1000 cycles is 52%. The initial discharge capacity at -20°C is 117mAh / g, and the symmetrical battery cycle is 990 hours.
[0057] Example 6
[0058] Compared with Example 1, the only difference is that the thickness of the Z surface is 100 microns. Other operations, parameters and tests are the same as those in Example 1, and the results are: The first discharge capacity at 25°C is 249 mAh / g, and the capacity retention rate is 52% after 1000 cycles. The initial discharge capacity at -20°C is 120 mAh / g, and the symmetrical battery cycle is 1000 hours.
[0059] Example 7
[0060] Compared with Example 1, the only difference is that the thickness of the G surface is 700 microns. Other operations, parameters and tests are the same as those in Example 1, and the results are: The first discharge capacity at 25°C is 238 mAh / g, and the capacity retention rate is 47% after 1000 cycles. The initial discharge capacity at -20°C is 108 mAh / g, and the symmetrical battery cycle is 860 hours.
[0061] Example 8
[0062] Compared with Example 1, the only difference is that the spinning speed of the two stages is 0.03 ml / min. Other operations, parameters and tests are the same as those of Example 1, and the results are: The first discharge capacity at 25°C was 259 mAh / g, and the capacity retention rate was 54% after 1000 cycles. The initial discharge capacity at -20°C was 118 mAh / g, and the symmetrical battery cycle was 990 hours.
[0063] Example 9
[0064] Compared with Example 1, the only difference is that the polymers in the spinning solution A and the spinning solution B are changed, and the experimental groups are respectively: Group A: The polymers in both spinning solution A and spinning solution B are PAN, and other operations and parameters are the same as those in Example 1.
[0065] Group B: The polymers in both spinning solution A and spinning solution B are the PAA, and other operations and parameters are the same as those in Example 1.
[0066] The test was carried out according to the method of Example 1, and the results were: Group A: The first discharge capacity at 25°C was 239 mAh / g, and the capacity retention rate was 45% after 1000 cycles. The initial discharge capacity at -20°C was 105 mAh / g, and the symmetrical battery cycled for 845 hours.
[0067] Group B: The first discharge capacity at 25°C was 236 mAh / g, and the capacity retention rate was 46% after 1000 cycles. The initial discharge capacity at -20°C was 108 mAh / g, and the symmetrical battery cycled for 860 hours.
[0068] Example 10
[0069] Compared with Example 1, the only difference is that the content of polymer P1 in spinning solution A is 15wt.%, and the content of polymer P2 in spinning solution B is 18wt.%; the voltage of the two stages of electrospinning is 16kV, and other operations and parameters are the same as Example 1.
[0070] The first discharge capacity at 25°C was 259 mAh / g, and the capacity retention rate was 55% after 1000 cycles. The initial discharge capacity at -20°C was 121 mAh / g, and the symmetrical battery cycled for 1090 hours.
[0071] Comparative Example 2
[0072] Compared with Example 1, after spinning in step 2, drying is performed to obtain a first fiber material; in step 3, aluminum foil is used as a substrate, and the second fiber material is formed under the conditions of step 3; the first fiber material and the second fiber material, which are independent of each other, are assembled according to the structural relationship of Example 1 to obtain a battery, and the battery is tested. The first discharge capacity of the cycle at 25°C is 186mAh / g, and the capacity retention rate after 1000 cycles is 42%. The initial discharge capacity at -20°C is 96mAh / g, and the symmetrical battery cycle is 780 hours.
[0073] Comparative Example 3
[0074] Compared with Example 1, the only difference is that the spinning solution in step 2 is spinning solution B, and the other operations and parameters are the same as Example 1. The first discharge capacity of the cycle at 25°C is 223 mAh / g, and the capacity retention rate after 1000 cycles is 41%. The initial discharge capacity at -20°C is 98 mAh / g, and the symmetrical battery cycle is 810 hours.
Claims
1. A method for preparing a zinc-P1 / P2 double-layer composite fiber electrode, characterized in that: Obtaining a spinning solution A in which zinc salt and polymer P1 are dissolved, and obtaining a spinning solution B in which polymer P2 is dissolved; The first stage of electrostatic spinning is carried out using spinning solution A to obtain a zinc-P1 layer; the second stage of electrostatic spinning is carried out using the zinc-P1 layer as a substrate using spinning solution B to form a P2 layer on the surface of the zinc-P1 layer, which is then dried to obtain the zinc-P1 / P2 double-layer composite fiber electrode.
2. The method for preparing the zinc-P1 / P2 double-layer composite fiber electrode according to claim 1, characterized in that: The zinc salt is one or more of zinc chloride, zinc trifluoromethanesulfonate, zinc sulfate, bis(trifluoromethanesulfonyl)zinc, zinc acetate, and zinc perchlorate; preferably at least one of zinc trifluoromethanesulfonate and bis(trifluoromethanesulfonyl)zinc.
3. The method for preparing the zinc-P1 / P2 double-layer composite fiber electrode according to claim 1, characterized in that: The polymer P1 and polymer P2 are one or more of polyacrylonitrile PAN, polyacrylic acid PAA, and polyvinyl pyrrolidone PVP; Preferably, the polymer P1 and polymer P2 are different polymers; Preferably, the polymer P1 is PAN, and the polymer P2 is PAA.
4. The method for preparing the zinc-P1 / P2 double-layer composite fiber electrode according to claim 1, characterized in that: The solvents in the spinning solution A and the spinning solution B include one or more of N,N-dimethylformamide DMF, N,N-dimethylacetamide DMA, etc.; Preferably, the solvent in spinning solution A is DMF, and the solvent in spinning solution B is DMA; Preferably, the content of zinc salt is 5-30 wt .%, and can further be 10-25 wt .%; the content of polymer P1 is 1-40 wt .%, and can further be 10-25 wt .%; Preferably, in the spinning solution B, the content of polymer P2 is 5~50 wt.%.
5. The method for preparing the zinc-P1 / P2 double-layer composite fiber electrode according to claim 1, characterized in that: The voltage of electrospinning is 12~18kV; Preferably, the thickness of the zinc-P1 layer is 20-100 μm; the thickness of the P2 layer is 200-700 μm.
6. The method for preparing the zinc-P1 / P2 double-layer composite fiber electrode according to claim 1, characterized in that: The speed of the first electrospinning stage and the second electrospinning stage was 0.01-0.05 mm min -1 ; Preferably, the spinning speed of the first stage of electrospinning is 0.01-0.03 ml min -1 The spinning speed of the second electrospinning stage was 0.03-0.05 ml min -1 , and the rate of the second electrospinning stage is 1.5~2.5 times that of the first electrospinning stage.
7. The method for preparing the zinc-P1 / P2 double-layer composite fiber electrode according to claim 1, characterized in that: The drying temperature is 45~70℃.
8. A zinc-P1 / P2 double-layer composite fiber electrode prepared by the preparation method according to any one of claims 1 to 7.
9. An application of a zinc-P1 / P2 double-layer composite fiber electrode prepared by the preparation method according to any one of claims 1 to 7, characterized in that: It is used to prepare negative electrode-free zinc batteries; Preferably, the zinc-P1 / P2 double-layer composite fiber electrode and the positive electrode are combined to form a battery cell of a negative-electrode-free zinc battery without adding a separate separator, wherein the surface of the P2 layer of the zinc-P1 / P2 double-layer composite fiber electrode is close to the positive electrode side; Preferably, the negative electrode-free zinc battery further comprises an aqueous electrolyte.
10. A negative electrode-free zinc battery, characterized in that: It comprises a zinc-P1 / P2 double-layer composite fiber electrode and a positive electrode composite battery cell prepared by the preparation method described in any one of claims 1 to 7, and an electrolyte for immersing the battery cell, wherein the surface of the P2 layer of the zinc-P1 / P2 double-layer composite fiber electrode is close to the positive electrode side.
Citation Information
Patent Citations
Negative-electrode-free zinc battery with high safety coefficient and low cost and application of negative-electrode-free zinc battery
CN113013496A
High-performance negative-electrode-free aqueous zinc metal battery based on composite layered negative electrode current collector
CN115764005A
CNF-GeO<2>-Li composite electrode applied to lithium metal battery and preparation method of CNF-GeO<2>-Li composite electrode
CN112838203A
High-energy-density high-safety negative-electrode-free zinc metal battery as well as preparation method and application thereof
CN113036152A
Porous fiber silica negative electrode composite material and preparation method thereof
CN113201808A